THE EFFECT OF MAULI BANANA STEM (Musa acuminata) AND BASIL LEAF (Ocimum basilicum L.) EXTRACT ON THE VALUE OF DIAMETRAL TENSILE STRENGTH OF BIOACTIVE COMPOSITE RESIN - Dewi Puspitasari; Annisa Aulia Rahmah; Maharani Laillyza Apriasari (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Chemical contents in mouthwash could cause several side effects in the oral cavity, hence natural ingredients were used such as Mauli banana stem and basil leaf extract. Mouthwash exposure in the oral cavity affects composite resin, one of it is a bioactive composite resin which has advantages over conventional ones. The contact of mouthwash with bioactive composite resin affects strength properties. Purpose: To analyse the effect of Mauli banana stem and basil extract on the diametral tensile strength value of the bioactive composite resin. Method: Thirty specimens (diameter 6mm x thickness 3mm; n=5/ group) were made using Activa™ Bioactive Restorative (Pulpdent) and immersed in the following group of 25%, 50%, 75% and 100% Mauli banana stem and basil leaf extract as a treatment groups, chlorhexidine gluconate 0,2 % (CHX) and aquadest as a control groups for 24 hours in the incubator at 37oC. Diametral tensile strength value was measured by Universal Testing Machine (Tokyo Testing Machine MFG CO.LTD) with 0,5 mm/minute crosshead speed and 250 kgF load cell. Result: One Way Anova and Post Hoc Bonferroni show there is a significant difference between treatment groups of 25% extract (41,33±6,20 MPa) and treatment groups of 100 % extract (55,06±6,42 MPa). Meanwhile, there is no significant difference for other groups. Conclusion: There is a significant effect of Mauli banana stem and basil leaf extract on the diametral tensile strength value of bioactive composite resin.